Construction of a low molecular weight plasmid vector for the capture of genes encoding exported proteins - YU Xu-ping; ZHU Jun-li; YAO Xue-ping; HE Shi-cheng; NIU Dong (浙江大学学报. 农业与生命科学版)
A pair of primers were designed to amplify a fragment of AMP gene, encoding merely mature part of β-lactamase with no promoter and signal peptide (△P△SP Amp), from pUC18. The gene was cloned into pGEM-T-EASY vector, and cut with EcoR Ⅰ. The recovered △P△SP Amp gene was then cloned and inserted between EcoR Ⅰ and Xba Ⅰ sites of plasmid pKan, derived from plasmid pET-28. Thus it resulted in a plasmid pMBL-E, with which the host could grow on plate with Kan but not with both Amp and Kan. The plasmid pMBL-E was then partially digested with EcoR Ⅰ, filled and self-ligated. A vector pMBL, about 3.46 kb in size, for the capture of the genes encoding exported proteins was finally selected, in which the EcoR Ⅰ site beside Hind Ⅲ site on pMBL-E was deleted. Both results of the restriction enzyme digestion and sequencing demonstrated the correctness of the construction. The effectiveness of the vector was verified, using a 375 bp Tetr gene fragment of pBR322, which showed that the pMBL vector would effectively clone genes encoding exported proteins with promoters and signal peptide sequences.